Amino acid functionalised calixarenes: crystal growth modifiers and low molecular weight gelators - Goh, Ching Yong (Curtin University, 2012)
A selection of amino acid functionalised calix[4]arenes was studied. Acidic amino acid functionalised calixarenes were investigated as crystal growth modifiers. The self-assembly behaviour of proline functionalised calixarenes were also examined.Calix[4]arenes functionalised at the wide-rim with acidic amino acids were investigated as potential crystal growth modifiers on model mineral systems and were compared with previously investigated narrow-rim analogues. This study found that the wide-rim aspartic acid and glutamic acid functionalised calix[4]arenes had an impact on the morphology of calcium carbonate and barium sulfate. The iminodiacetic acid calix[4]arene was found to have minor impact on the morphology of calcium carbonate.In comparison with the narrow-rim analogues, the wide-rim and narrow-rim aspartic acid calix[4]arenes had similar potency on calcium carbonate while the wide-rim glutamic acid calix[4]arene appeared to be more potent than the narrow-rim calix[4]arene. Calcium carbonate crystallised in the presence of wide-rim aspartic acid and glutamic acid calix[4]arenes and their narrow-rim analogues had stepped edges which resembled calcium carbonate found in biomineral systems (e.g. mollusc shells). Desupersaturation experiments showed the wide-rim aspartic acid calix[4]arene to be a more potent inhibitor of barium sulfate crystallisation than the wide-rim glutamic acid calix[4]arene.An aqueous solution of L-proline calix[4]arene exhibited surfactant-like properties. The self-assembly behaviour of L-proline calix[4]arene in solution was characterised by UV-visible and NMR spectroscopy. The critical aggregation concentration of L-proline calix[4]arene was determined to be 4–9 mM by monitoring a selection of dye compounds using UV-visible spectroscopy. The interaction of L-proline calix[4]arene with small molecules and in the presence of electrolytes was also characterised by NMR spectroscopy. The 1H NMR spectra of L-proline calix[4]arene in the presence of small molecules (tetrahydrofuran, 1-methyl-2-pyrrolidinone, and tert-butyl alcohol) suggested that the calixarene was either acting as a host or selfassembling into larger aggregates. Variable temperature NMR experiments showed that these interactions were thermoreversible.The formation of a hydrogel by proline calix[4]arenes in the presence of electrolytes was a serendipitous discovery. Investigations with selected electrolytes showed that the anion was the dominant factor in determining if a hydrogel formed, with lesser influence from the cation. The thermostability of the calixarene-electrolyte hydrogels tended to follow the Hofmeister series, where more stable hydrogels formed in the presence of anions towards the chaotropic end of the series. A racemic mixture of the proline calixarenes gave a less stable hydrogel compared with hydrogels of the enantiopure compounds. The calixarene-electrolyte hydrogels had a fibrous appearance, as characterised by atomic force microscopy. Some hydrogels collapsed slowly and deposited crystals of sufficient quality for single crystal x-ray crystallography. These structures gave some insights into how intermolecular forces may give rise to the fibrous gel structures; in particular hydrogen bonds between proline moieties, and the inclusion of a proline group into the cavity of a neighbouring calixarene, leading to spiral-like structures. A sarcosine functionalised calix[4]arene also formed hydrogels upon addition of some electrolytes, whereas the proline-functionalised calix[5]arene analogue did not.Since a range of hydrogels have been used as matrices to control crystal growth, a proline calix[4]arene-lithium nitrate hydrogel was used as a potential template for barium sulfate crystallisation. The results suggested that lithium nitrate was the main factor in modification of the barium sulfate morphology. The hydrogel did have a minor impact by slowing the diffusion of sulfate anions into the barium-containing gel phase resulting in smaller particles.The versatility of amino acid functionalised calix[4]arenes has been highlighted here. Wide-rim functionalised acidic amino acid calix[4]arenes were found to be effective crystal growth modifiers; having an impact on the morphology and growth kinetics of model crystallisation systems, calcium carbonate and barium sulfate. Interesting supramolecular chemistry was observed with proline functionalised calix[4]arenes; the proline calixarene interacts with small molecules in solution and either act as a host or self-assembles into large aggregates. The formation of proline calix[4]arene aggregates is interesting as they give rise to hydrogels in the presence of selected electrolytes.